STUDI ATAS IMPLEMENTASI SISTEM INFORMASI BERBASIS KOMPUTER UNTUK MENGENDALIKAN KEGIATAN PEMBELIAN DI PERUSAHAAN TEKSTIL HM DI BANDUNG - Elizabeth T. Manurung; Lenny . (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
The objective of this study is to evaluate the implementation of the information system based on technology which is related to purchasing activity control. This evaluation uses general control and application control. The study result shows that general control aspect was satisfied and it’s proving by: (a) satisfying management IT personnel department; (b) safety physical and online access; (c) company has backup data procedure; (d) satisfy control of hardware system. Another control from application aspect are: input control has satisfied validity check that automatically making comparison between purchases transaction code with standard coding number; processing control has satisfied recalculation of batch totals check that doing recalculation total batch of each purchase transaction; and output control has satisfy reconciliation check procedure that automatically making accounts reconciliation example from purchases general ledger with accounts payable subsidiary ledger. All those controls proving us that the risk in purchasing activities can be reduced, and it means purchases activities can be well controlled